2016
DOI: 10.1590/s1980-5764-2016dn1003003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive stimulation on neuropsychiatric symptoms in elderly with Alzheimer's disease: A systematic review

Abstract: Introduction: Neuropsychiatric symptoms are frequent in Alzheimer's disease and negatively affect patient quality of life. Objective: To assess the effectiveness of cognitive stimulation on neuropsychiatric symptoms in elderly patients with Alzheimer's disease. Methods: The included articles were reviewed between December 2015 and June 2016, and the inclusion criteria were: (1) studies involving older adults diagnosed with Alzheimer's disease; (2) studies published in English, Spanish or Portuguese; (3) studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
(77 reference statements)
1
12
0
Order By: Relevance
“…A systematic review 55 found that exercise has a positive effect on overall cognitive function and may slow the rate of cognitive decline in people with Alzheimer's dementia. A systematic review 56 found that cognitive stimulation had beneficial effects on cognitive function and some aspects of well‐being in people with Alzheimer's dementia. Another systematic review 57 reported that cognitive stimulation was associated with improved scores on tests of depression in people with mild‐to‐moderate Alzheimer's dementia. A summary of systematic reviews 58 reported that cognitive stimulation, music‐based therapies and psychological treatment (for example, cognitive behavioral therapy) improved depression, anxiety and quality of life in people with dementia. A summary of systematic reviews 59 of cognitive training for people with mild‐to‐moderate dementia found cognitive training may show some benefits in overall cognition that may last for at least a few months.…”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…A systematic review 55 found that exercise has a positive effect on overall cognitive function and may slow the rate of cognitive decline in people with Alzheimer's dementia. A systematic review 56 found that cognitive stimulation had beneficial effects on cognitive function and some aspects of well‐being in people with Alzheimer's dementia. Another systematic review 57 reported that cognitive stimulation was associated with improved scores on tests of depression in people with mild‐to‐moderate Alzheimer's dementia. A summary of systematic reviews 58 reported that cognitive stimulation, music‐based therapies and psychological treatment (for example, cognitive behavioral therapy) improved depression, anxiety and quality of life in people with dementia. A summary of systematic reviews 59 of cognitive training for people with mild‐to‐moderate dementia found cognitive training may show some benefits in overall cognition that may last for at least a few months.…”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…A systematic review 53 found that exercise has a positive effect on overall cognitive function and may slow the rate of cognitive decline in people with Alzheimer's dementia. A systematic review 54 found that cognitive stimulation had beneficial effects on cognitive function and some aspects of well‐being in people with Alzheimer's dementia. Another systematic review 55 reported that cognitive stimulation was associated with improved scores on tests of depression in people with mild‐to‐moderate Alzheimer's dementia. A 2019 summary 56 of systematic reviews reported that cognitive stimulation, music‐based therapies and psychological treatment (for example, cognitive behavioral therapy) improved depression, anxiety and quality of life in people with dementia. A 2019 summary of systematic reviews 57 of cognitive training for people with mild‐to‐moderate dementia found cognitive training may show some benefits in overall cognition that may last for at least a few months.…”
Section: Overview Of Alzheimer's Diseasementioning
confidence: 99%
“…• A systematic review 54 found that cognitive stimulation had beneficial effects on cognitive function and some aspects of well-being in people with Alzheimer's dementia. Another systematic review 55 reported that cognitive stimulation was associated with improved scores on tests of depression in people with mild-to-moderate Alzheimer's dementia. A 2019 summary 56 of systematic reviews reported that cognitive stimulation, music-based therapies and psychological treatment (for example, cognitive behavioral therapy) improved depression, anxiety and quality of life in people with dementia.…”
Section: Non-pharmacologic Therapymentioning
confidence: 99%
“…Two systematic reviews of systematic reviews (Abraha et al, 2017;Vilela, Pacheco, Latorraca, Pachito, & Riera, 2017) reveal that non-pharmacological interventions have positive effects on reducing BPSD, improving cognitive function, activities of daily living, and social interaction ability of patients with dementia. For apathy, there are several systematic reviews and meta-analyses (Brodaty & Burns, 2012;Fukushima et al, 2016;Goris, Ansel, & Schutte, 2016;Lane-Brown & Tate, 2009;Theleritis, Siarkos, Katirtzoglou, & Politis, 2016;Theleritis, Siarkos, Politis, Katirtzoglou, & Politis, 2018;Tsoi et al, 2018;Verkaik, Weert, & Francke, 2005;Zafra-Tanaka, Pacheco-Barrios, Tellez, & Taype-Rondan, 2019) of non-pharmacological interventions in patients with dementia. Nevertheless, these reviews involve diversified non-pharmacological interventions and lack evaluation of methodological quality and classification of evidence quality.…”
Section: Introductionmentioning
confidence: 99%